Environmental controls on the distribution of salt‐marsh foraminifera from the southern coastline of South Africa - Kate L. Strachan; Jemma M. Finch; Trevor R. Hill; Robert L. Barnett; Craig D. Morris; Peter Frenzel (Journal of Biogeography, 2016)
Aim Salt‐marsh foraminifera are widely used as robust sea‐level indicators. High‐resolution Holocene sea‐level reconstructions depend on the accurate characterization of modern foraminifera‐environment relationships representative of a study site. We investigate the relationship between modern foraminiferal assemblage distribution and key environmental variables, viz . elevation above land levelling datum ( LLD ), sediment grain size, organic content, pH and salinity. We hypothesize that the distribution of modern salt‐marsh foraminifera is primarily controlled by elevation above LLD . Location Knysna and Keiskamma estuaries along the southern coastline of South Africa. Methods Salt‐marsh surface sediment samples ( n = 97) were collected along eight intertidal transects with corresponding environmental data ( pH , salinity, organic content, sand, silt, clay and elevation). Multivariate ordination analysis (partial redundancy analysis; pRDA ) was used to investigate the relationship between living foraminiferal assemblages and environmental controls, after accounting for spatial variability in community composition. Results The pRDA suggests that species composition varied spatially within estuaries, but was strongly influenced by elevation at Keiskamma ( r = 0.63) and Knysna ( r = −0.75). At Keiskamma, the main gradient in composition was also influenced by salinity ( r = −0.63), in an equal and opposite manner to elevation. Composition at Keiskamma was influenced to a much lesser extent by sediment organic content ( r = 0.20) and the clay fraction ( r = −0.13). At Knysna, pH ( r = 0.455) was a secondary determinant of composition, and sediment characteristics covaried with elevation. Main conclusion Elevation was found to be a key environmental variable controlling the distribution of salt‐marsh foraminifera at both estuaries, thereby validating the use of foraminifera as sea‐level indicators. Certain species were particularly sensitive to elevation changes and could thus serve as useful indicators of past sea‐level change. This is an important first step towards the development of high‐resolution sea‐level reconstructions for the South African coastline.